AB0957 Severity of skin symptoms is not associated with musculoskeletal manifestations in patients with psoriasis. (12th June 2018) - Yamada, Y.; Inui, K.; Okano, T.; Sugioka, Y.; Yoshimura, H.; Mamoto, K.; Koike, T.; Tada, M.; Tateishi, C.; Yonezawa, E.; Natsumi, A.; Fukunaga, Y.; et al.
Abstract : Background: Among patients with psoriasis, risk factors for developing musculoskeletal manifestations, known as psoriatic arthritis (PsA), are not recognised well. Objectives: The aim of this study is to clarify the relationship between severity of skin disease and arthritis. Methods: Psoriasis patients referred from dermatologists for assessment of musculoskeletal manifestations between June 2015 and July 2017 were enrolled. Their age, comorbidity, disease duration and treatment were collected. Presence of inflammatory back pain, sacroiliac joint tenderness or enthesitis were examined. Severity of skin symptoms were evaluated by dermatologists in Psoriasis area and severity index (PASI). Psoriatic arthritis screening and evaluation (PASE) and disease activity score (DAS28 ESR) were also evaluated. PsA was diagnosed by The Classification for Psoriatic Arthritis (CASPAR) criteria assisted with musculoskeletal ultrasound examination. Results: Among 107 patients with psoriasis referred from dermatologists during designated period, 63 patients were diagnosed as PsA. These PsA patients were compared with 44 patients who had no arthritis (PsO). Multiple logistic regression analysis showed neither of age, sex, PASI, disease duration, rheumatoid factor (RF), CRP or Matrix Metalloproteinase-3 (MMP3) had no association with presence of PsA (table 1). Among 63 patients with PsA, those using NSAIDs (p=0.028), those with inflammatory back pain (p=0.002) and male patients (p=0.017) had significantly high PASI. PASI significantly correlated with age (Spearman's correlation coefficient R=−0.303: p=0.016), body height (R=0.301: p=0.019) and weight (R=0.383: p=0.002), but not with DAS28 ESR, MMP3 or disease duration (table 2). Table 1 multiple logistic regression analysis for presence of PsA Conclusions: PASI did not associate with presence of arthritis. Furthermore, even DAS28 ESR, reflecting musculoskeletal manifestations, or disease duration did not correlated with PASI among patients with PsA. These indicates severity of skin symptoms is not associated with musculoskeletal manifestations in patients with psoriasis. Disclosure of Interest: None declared